THE SUSTAINABILITY PARADOX: WHY FIRE-RESISTANT TEXTILES ARE THE BACKBONE OF A SAFE BUILT ENVIRONMENT - Manasieva, Kapka (E-Journal VFU, 2026)
This article examines the critical nexus between contemporary textile loads in the built environment and fire safety, analyzing the "Sustainability Paradox": the conflict between the use of eco-friendly, often recycled polymeric materials, and the dramatic increase in energy density within modern homes. The study analyzes the transformation of the variable fire load, highlighting the transition from cellulosic materials to petroleum-based synthetic structures. The text classifies the textile ecosystem according to international standards and reveals the inherent conflict between the low carbon footprint of recycled materials (rPET) and their high energetic risk. The research concludes with a conceptual model for sustainable security, in which fire resilience is positioned as a mandatory prerequisite for the genuine ecological sustainability of the built environment.